(untitled) (AmS-Skrifter, 2019)
People were usually buried in single, individual graves in Early Bronze Age Austria and the surrounding areas, but there are some exceptions. In burials of two or more people, it is often the way that bodies were placed in relation to each other that suggests familiarity, if not family. This paper reviews the social relations expressed through co-burials, and aims to better understand relationships between couples, siblings, or parents and children. The chapter particularly highlights mother-child relationships and presents graves of pregnant women and graves of women and children buried together, in order to understand how such individuals were treated by their societies in death. Ages and age gaps between co-buried individuals reveal the most likely ages for life-transitions such as first motherhood and the addition of new family members. The analysis compares evidence from two different, but contemporary cultural groups (Únětice and Unterwölbing) to shed light on prehistoric gender relations, family structures and social organisation through the lens of the burial record.